PANDANGAN ISLAM DAN PSIKOLOGI TERHADAP TRANSFORMASI PEREMPUAN - Nurussakinah Daulay (IAIN Ponorogo, 2015)
Abstract: Transformation of women, as a discourse and the idea of the movement, increasingly writhed after the International Women's Conference in Beijing in 1995. The big question is how to construct the transformation of women in the crush of fear of success through the frame of diverse perspectives. Through religion and psychology approach, this paper attempted to describe the transformation of women's movement which has been increasingly writhing in the era of globalization. The data of the religious texts including Islamic religious texts showed that there was an equality between men and women, and husband and wife which were not only related to their rights they possessed , but also related to the obligations that must be carried out. The transformation of women's movement, especially in the perspective of religion, found the historical momentum since the presence of Islam brought by Muhammad in the Arabian Peninsula. At this global era, the demands on a role in the public sphere increasingly crystallized so that women were also required to actualize themselves in various social entities. Self-actualization in a variety of careers turned out to be in the form of a direct proportional relationship with the emergence of anxiety that led to conflict between selfhood on one side with public opinion which regarded it as a masculine figure on the other. This anxiety appeared when they, the women, were trapped between trying to reach a great achievement and their own shadows.الملخص :تحوّل المرأة كموضوع حديث وفكرة الحركة أصبح ممتدّا بعد اللقاء العالمي للمرأة في بيجنج سنة 1995. والسؤال المطروح هو كيف تشكيل هذا التحوّل في محور fear of success في ضوء كثير من وجهات النظر. حاولت هذه الدراسة – بالمدخل الديني النفسي – تصوير حركة تحوّل المرأة المتطوّرة في عصر العولمة. دلّت البيانات من النصوص الدينية أن هناك مساواة وتواز بين الرجل والمرأة وفي الأسرة بين الزوج والزوجة، كل منهما له حقوق وواجبات. هذه الحركة النسائية – خاصة في منظار ديني - تجد فرصتها التاريخية المناسبة منذ ظهور الإسلام في الجزيرة العربية. وفي هذا العصر هناك متطلبات لظهور ودور المرأة في المجتمع. والواقع أن اتخاذ المرأة هذا الدور – في كثير من المناصب – أدي إلى نشوء الشعور بالهموم على الوعي بالنفس في جانب وبرأي المجتمع عنها في جانب آخر لأنهم اعتبرها امرأة. إذن وقعت المرأة في همّ بين المحاولة للحصول على الانجازات وظلّ نفسها.Abstrak: Transformasi perempuan, sebagai sebuah wacana dan ide gerakan, semakin menggeliat pasca Konferensi Perempuan Internasional di Beijing pada tahun 1995. Pertanyaan besarnya adalah bagaimana mengkonstruk transformasi perempuan dalam himpitan fear of success melalui bingkai beragam perspektif. Melalui pendekatan agama dan psikologi, tulisan ini mencoba untuk mendiskripsikan gerakan transformasi perempuan yang kian menggeliat di era globalisasi. Data-data teks keagamaan termasuk Islam menunjukkan bahwa terdapat kesetaraan antara laki-laki dan perempuan, terdapat equalitas antara suami dan istri tidak saja terkait dengan hak yang mereka miliki tetapi juga terkait dengan kewajiban yang harus diemban. Gerakan transformasi perempuan ini, khususnya dalam perspektif agama, menemukan momentum historisnya sejak kehadiran Islam yang dibawa oleh Muhammad saw di Jazirah Arab. Pada era global ini tuntutan peran dalam ranah publik semakin mengkristal sehingga perempuan juga dituntut untuk mengaktualisasikan diri dalam beragam entitas sosial. Aktualisasi diri dalam beragam karir ternyata berbanding lurus dengan munculnya kecemasan yang melahirkan konflik antara kedirian di satu sisi dengan opini publik yang menganggapnya sebagai sosok yang maskulin. Muncul kecemasan bahwa mereka, para perempuan, terjebak antara usaha meraih prestasi dengan bayangan diri. Keywords: transformasi, perempuan, Islam, psikologi, aktualisasi, fear of success.